The Impact of the Digital Economy on Carbon Emissions: Evidence from China - Lyu, Xinying (Journal of Empirical Studies, 2022)
To achieve net-zero carbon dioxide emissions, countries including China have taken actions to transform their energy-intensive industries and optimize their energy consumption structure. One possible way is to integrate the development of the digital economy into the green-economy efficiency promotion. This study examines the effects of the development in the digital economy on carbon emissions based on the panel data of 31 provinces in mainland China spanning from 2009 to 2019. The regression results show that there was a negative relationship between the digital economy and carbon emissions, which seems to run counter to the prior hypothesis. This is probably because since the beginning of this period China has already been taking advantages of developments in the digital economy to reduce carbon dioxide pollution. Based on the empirical results, I suggest that the digital economy be used to increase the overall productivity and efficiency of the economy, especially in under-developed areas like the northeastern region.